Simultaneous repair of bilateral temporal bone meningoencephaloceles by combined mastoid-middle cranial fossa approach - Kazuto Osaka; Takayuki Okano; Masahiro Tanji; Koichi Omori (Acta Oto-Laryngologica Case Reports, 2023)
AbstractMeningoencephalocele (MEC) is a rare clinical entity caused by herniation of the dura mater and brain tissue through bony defects in the skull base. We herein report a case of bilateral MECs found after recurrent bacterial meningitis. The patient subsequently underwent simultaneous bilateral resection of the MECs and repair of the lateral skull base using a combined mastoid-middle cranial fossa approach. The bone and dura were reconstructed using free bone grafts and a temporalis fascia flap. Three years after surgery, temporal bone computed tomography showed that the reconstructed tegmen was preserved bilaterally, and there was no recurrence of meningitis or MECs. The appropriate surgical approach should be chosen based on the localization and size of the herniated tissue, and the presence of active infection or other coexisting pathology. Simultaneous bilateral resection using the combined mastoid-middle cranial fossa approach is a promising option for the treatment of bilateral multiple MECs.